Estimating the real effects of uncertainty shocks at the zero lower bound - Giovanni Caggiano; Efrem Castelnuovo; Giovanni Pellegrino (Bank of Finland, 2017)
We employ a parsimonious nonlinear Interacted-VAR to examine whether the real effects of uncertainty shocks are greater when the economy is at the Zero Lower Bound. We find the contractionary effects of uncertainty shocks to be statistically larger when the ZLB is binding, with differences that are economically important. Our results are shown not to be driven by the contemporaneous occurrence of the Great Recession and high financial stress, and to be robust to different ways of modeling unconventional monetary policy. These findings lend support to recent theoretical contributions on the interaction between uncertainty shocks and the stance of monetary policy.
URN:NBN:fi:bof-201702011089
Keywords: C32; E32; 330